2012
DOI: 10.1111/j.1532-950x.2012.01028.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Analysis of Twelve Toggle Suture Constructs for Stabilization of Coxofemoral Luxations

Abstract: A combination of the Piermattei toggle and #5 OrthoFiber or #5 Ethibond achieved a higher load at failure than all other groups, and resisted the greatest number of cycles to failure. Long-term mechanical testing of these TSCs are warranted to further define their durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 19 publications
3
30
0
Order By: Relevance
“…MNL is also less likely to harbour bacteria and become infected than multifilament materials (Lewis et al ). In contrast, three biomechanical studies reported that polyethylene blended suture materials were stiffer, stronger and elongated less than MNL (Burgess et al , Jha & Kowaleski , Rose et al ). Crimp clamps were used in this study as initial tension and stiffness have been reported to be greater for crimped loops when compared to knotted loops of 80 lb MNL in three in vitro studies (Banwell et al , Peycke et al , Vianna & Roe ).…”
Section: Discussionmentioning
confidence: 96%
“…MNL is also less likely to harbour bacteria and become infected than multifilament materials (Lewis et al ). In contrast, three biomechanical studies reported that polyethylene blended suture materials were stiffer, stronger and elongated less than MNL (Burgess et al , Jha & Kowaleski , Rose et al ). Crimp clamps were used in this study as initial tension and stiffness have been reported to be greater for crimped loops when compared to knotted loops of 80 lb MNL in three in vitro studies (Banwell et al , Peycke et al , Vianna & Roe ).…”
Section: Discussionmentioning
confidence: 96%
“…This study was designed to characterize further the mechanical performance of a synthetic implant commonly used for open surgical stabilization of coxofemoral luxation in dogs. Our mechanical testing set‐up, based on a prior bench top mechanical analysis of toggle suture constructs, introduced the variable of suture attachment method to the toggle. The 1/8‐in toggle rod is the most commonly used implant size reported in the veterinary literature for hip luxation repair .…”
Section: Discussionmentioning
confidence: 99%
“…Our mechanical testing set‐up, based on a prior bench top mechanical analysis of toggle suture constructs, introduced the variable of suture attachment method to the toggle. The 1/8‐in toggle rod is the most commonly used implant size reported in the veterinary literature for hip luxation repair . The mean weight reported in the literature for dogs with traumatic coxofemoral luxation and subsequent repair ranges from 15 kg to 29 kg, and the 1/8‐in toggle rod is the manufacturer‐recommended implant for dogs of this size .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations